"The English Language and Its Role in Developing Scientific Research in Iraqi Society" (Texas Journal of Multidisciplinary Studies, 2023)
The study dealt with the role of the English language in scientific research for social development in Iraq, as scientific research Is considered one of the most important means that help achieve scientific and technological social development. The study reviews the challenges that Iraqi researchers face in scientific research in English, Including poor access to scientific resources in English and lack of sufficient proficiency in the English language. The study also deals with the importance of learning English to improve the quality of social science research in Iraq, and the role of universities and educational institutions in improving the ability of students and researchers to use English in scientific research. The study recommends the need for more support and encouragement for Iraqi scientific researchers by providing scientific resources In English and providing students and researchers with educational programs in English in addition to science and culture. Exchange with English-speaking countries should be encouraged to increase the capacity of researchers and improve the quality of scientific research In Iraqi society